HUBUNGAN PENGETAHUAN GIZI DENGAN KEJADIAN DIABETES MELITUS (DM) TIPE II - Besti Verawati; Nopri Yanto; Ulfianti Gustiana (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2017)
Diabetes Mellitus (DM) Type II is a degenerative disease. One of the factors causing Type II diabetes is nutritional knowledge. The purpose of this study is to analyze the nutritional knowledge and with the incidence of type II DM in water in 2017. The design of this research is cross sectional study design. The population in this study is the adult group (30-49 years) amounted to 600 people and the sample in this study amounted to 88 people with the technique of Accidental Sampling (Accidental Sampling). The study was conducted on May 16-26, 2017. The measurement tool used questioner and glucometer. Analysis of univariate data in the form of frequency and percentage and bivariate with statistical assessment. The results showed 41 (46,6%) of respondents mostly have good knowledge of nutrition, that is 48 (47,7%). The result of bivariate have relationship between nutritional knowledge with DM Type II incidence (p <0,05)